The Four Necessities of Buddhist Monks: Patterns, Faiths, and Signs Changes in Luang Prabang, Laos - Chookaew, Padsarath; Phoomalee, Nongnuch; Apirating, Preechawut (International Journal of Membrane Science and Technology, 2023)
Luang Prabang was the early capital of the Laos PDR with national unification where the head of the state at that time was the monarchy, based on the Buddhist concept of centralization, and with the constitution based on Buddhist principles which originated from the belief that if the Lao leaders of any era were Buddhists, then there would be support for Buddhism and would bring prosperity and stability to Buddhism. Therefore, this research article aims to study the current condition of the Four Necessities of Buddhist Monks in Luang Prabang, Lao PDR. After being registered as a World Heritage City. This was a qualitative study by studying both documented data and fieldwork interviews with knowledgeable groups, practitioners, and relevant groups, and then analyzing the data descriptively using relevant theoretical framework analysis. The study found that when Luang Prabang was listed as a UNESCO World Heritage City in 1995, Luang Prabang became a world-class cultural tourism industry city, and its Buddhist roots remained. There was a preservation of patterns of life, culture, traditions, and unique traditional beliefs that had been handed down since the ancestors of the locals. After being registered as a World Heritage City, under the change of cultural traditions in Buddhism through merit-making by offering the Four Necessities of a Buddhist Monk, there is a practice that is currently focused on convenience and speed. Most of them are offered by you or purchased from stores available in Luang Prabang, with the main objective still continuing to offer Four Necessities to escape misfortune and create merit both for yourself in the present and in the next life.